Decay and persistence of maternal dengue antibodies among infants in Bangkok - Willem G. Van Panhuis (2018)
Maternal dengue antibodies are important in determining the optimal age of dengue vaccination, but no study has quantified the heterogeneity of antibody decay and persistence in infants. We used longitudinal regression methods and survival analysis to measure decay and persistence times of serotype-specific neutralizing antibodies in 139 infants in Bangkok. A biphasic decay pattern was found with half-life times of 24-29 days between birth and 3 months and 44-150 days after 3 months. Atypical decay rates were found in 17% of infants for dengue virus-1 and-4. Median persistence times of plaque reduction neutralization tests > 10 ranged from 6 to 9 months. Persistence times for individuals could not be predicted based on antibody values at birth. Vaccination against dengue before 12 months of age would be ineffective if maternal antibodies at plaque reduction neutralization test levels below 80 interfere with vaccine uptake. Projections of average antibody persistence based on values at birth should be avoided in studies on dengue pathogenesis in infants. Copyright © 2011 by The American Society of Tropical Medicine and Hygiene.